Beyond `crude pragmatism` in sports coaching: Insights from C.S. Peirce, William James and John Dewey: A Commentary - Shier, D. (International Journal of Sports Science & Coaching, 2017)
Jenkins succeeds in suggesting directions in which sports coaching can draw ideas from the works of classical pragmatists and move beyond "crude pragmatism." I have argued that many of the core features of classical pragmatism that make it useful to sports coaching are shared by the method of wide reflective equilibrium, and so we may expect that attention to reflective equilibrium may be similarly useful. FROM AUTHOR